A Comprehensive Review on Pharmacological Properties of Coumarins - Tejal Kaushik; Parnika Vashist; Surya Prakash D.V. (International Journal of Biochemistry and Biomolecule Research, 2024)
Coumarins are a diverse group of secondary metabolites found in a variety of plant species (over 1200 different coumarins have been identified from natural sources, especially plants), as well as in fungi and microorganisms. Coumarin is a simple, widely occurring chemical structure in nature, present in many plants, fungi, and bacteria. In recent years, these natural compounds have attracted growing interest from the scientific community due to their broad spectrum of biological activities, primarily because of their ability to interact with various enzymes and receptors in living organisms. Furthermore, the coumarin structure is easy to synthesize and modify, offering opportunities to design new coumarin-based compounds and explore their potential in treating various diseases. The flexibility of the coumarin scaffold makes it useful not only in medicinal chemistry but also in the agrochemical industry and the cosmetics and fragrance sectors. Coumarins possess several advantageous properties, such as low molecular weight, a simple structure, high bioavailability, excellent solubility in most organic solvents, and low toxicity. These features, combined with their wide-ranging biological effects, make them promising lead compounds in drug discovery. Coumarins demonstrate a variety of pharmacological effects, including antimicrobial, anticoagulant, neuroprotective, anti-inflammatory, antidiabetic, and anticonvulsant properties. They are also valuable in the food industry, where their fungicidal and antioxidant activities are being explored and utilized.
Keywords: Coumarins; Metabolites; Synthesis; biological activity; natural sources